2020
DOI: 10.1056/nejmoa1915928
|View full text |Cite
|
Sign up to set email alerts
|

Vericiguat in Patients with Heart Failure and Reduced Ejection Fraction

Abstract: BACKGROUND The effect of vericiguat, a novel oral soluble guanylate cyclase stimulator, in patients with heart failure and reduced ejection fraction who had recently been hospitalized or had received intravenous diuretic therapy is unclear. METHODS In this phase 3, randomized, double-blind, placebo-controlled trial, we assigned 5050 patients with chronic heart failure (New York Heart Association class II, III, or IV) and an ejection fraction of less than 45% to receive vericiguat (target dose, 10 mg once daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
852
4
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 930 publications
(1,069 citation statements)
references
References 18 publications
24
852
4
45
Order By: Relevance
“…Based on the results of SOCRATES-REDUCED [189] and SOCRATES-PRESERVED [190], VICTORIA [191], a multicentre, randomized, doubleblind, placebo-controlled trial of the efficacy and safety of the oral soluble guanylate cyclase stimulator vericiguat was carried out among a broadly generalizable high-risk population of three unique clinical strata of patients with worsening chronic HFrEF despite very good HF therapy [192]. The latest results showed that the incidence of death from cardiovascular causes or HHF was lower among those who received vericiguat than among those who received placebo [193]. In addition, the REDUCE LAP-HF study, an open-label, single-arm, phase I study designed to assess the performance and safety of a transcatheter interatrial shunt device in patients older than 40 years of age with symptoms of HFpEF despite pharmacological therapy, showed that the implantation of an interatrial shunt device is feasible, seems to be safe, reduces left atrial pressure during exercise, and could be a new strategy for the management of HFpEF [194].…”
Section: Future Directions In Finding Novel Treatments For Hfmentioning
confidence: 99%
“…Based on the results of SOCRATES-REDUCED [189] and SOCRATES-PRESERVED [190], VICTORIA [191], a multicentre, randomized, doubleblind, placebo-controlled trial of the efficacy and safety of the oral soluble guanylate cyclase stimulator vericiguat was carried out among a broadly generalizable high-risk population of three unique clinical strata of patients with worsening chronic HFrEF despite very good HF therapy [192]. The latest results showed that the incidence of death from cardiovascular causes or HHF was lower among those who received vericiguat than among those who received placebo [193]. In addition, the REDUCE LAP-HF study, an open-label, single-arm, phase I study designed to assess the performance and safety of a transcatheter interatrial shunt device in patients older than 40 years of age with symptoms of HFpEF despite pharmacological therapy, showed that the implantation of an interatrial shunt device is feasible, seems to be safe, reduces left atrial pressure during exercise, and could be a new strategy for the management of HFpEF [194].…”
Section: Future Directions In Finding Novel Treatments For Hfmentioning
confidence: 99%
“…This compound was studied in patients with systolic dysfunction in a high quality randomized clinical trial. Compared to placebo, treatment with vericiguat reduced hospitalizations and cardiovascular death among patients with systolic dysfunction [ 91 ]. This represents a significant breakthrough for clinical management of heart failure with a medication that utilizes a novel mechanism of action.…”
Section: Post-translational Modifications Of Titin Affect Myocardimentioning
confidence: 99%
“…Experimentell ist Vericiguat mit vielfältigen positiven Eigenschaften für das Herz wie bspw. der Reduktion der myokardialen Hypertrophie, der Reduktion von Fibrose und der Reduktion des systemischen und pulmonalvaskulären Widerstandes verbunden [23].…”
Section: Vericiguatunclassified
“…5000 Patienten mit symptomatischer (und akuter) Herzinsuffizienz und einer LVEF < 45 % den kombinierten Endpunkt aus Hospitalisation für Herzinsuffizienz und kardiovaskulärer Mortalität bei ähnlichem Nebenwirkungsspektrum wie Placebo um ca. 10 % reduzieren [23]. Betrachtete man die Endpunkte separat, konnte tatsächlich die Hospitalisationsrate, nicht aber die kardiovaskuläre Mortalität gesenkt werden.…”
Section: Vericiguatunclassified